Field switching of microfabricated metamagnetic FeRh MRI contrast agents - Stephen Dodd; Natalia Gudino; Oleksii Zadorozhnii; Michal Staňo; Jan Hajduček; Jon Ander Arregi; H. Douglas Morris; Vojtěch Uhlíř; Mladen Barbic; Alan P. Koretsky (Scientific Reports)
Abstract In a step towards generating switchable MRI cellular labels, we demonstrate in-situ field switching of micron scale metamagnetic Iron-Rhodium (FeRh) thin film particles. A thin-film (200 nm) FeRh sample was fabricated and patterned into an array of progressively smaller squares with sizes ranging from 500 μm down to 1 μm. The large first order phase change from antiferromagnetic to ferromagnetic state was characterized using vibrating sample magnetometry, magnetic force microscopy, and MRI. Room temperature MRI experiments sensitive to the local magnetic field surrounding the particles demonstrated the low moment state (OFF MRI contrast) at 4.7T and high moment state (ON MRI contrast) at 11.7T for the array where sizes down to 2–3 μm were observed in MRI at 50 μm resolution. The expected temperature dependent MRI contrast change was seen at 4.7T, where 10 μm particles could be observed at 150 μm resolution in the ON state. A shielded MRI insert, used to temporarily increase or decrease the magnetic field up to 0.77T amplitude, was used to reversibly switch the particle array at constant temperature and blink the particles ON and OFF at 4.7T. This work demonstrates the MRI contrast switching potential for FeRh particles with biological cell dimensions, and the use of magnetic field pulses for reversible MRI label contrast control.